1997
DOI: 10.1161/01.atv.17.11.2479
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Multiple Isoforms of Nitric Oxide Synthase in Normal and Atherosclerotic Vessels

Abstract: Atherosclerosis is associated with reduced endothelium-derived relaxing factor bioactivity. To determine whether this is due to decreased synthesis of nitric oxide synthase (NOS), we examined normal and atherosclerotic human vessels by in situ hybridization and immunocytochemistry by using probes specific for endothelial (ecNOS), inducible (iNOS), and neuronal (nNOS) NOS isoforms, ecNOS was detected in endothelial cells overlying normal human aortas, fatty streaks, and advanced atherosclerotic lesions. A compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
318
3
11

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 424 publications
(342 citation statements)
references
References 53 publications
10
318
3
11
Order By: Relevance
“…This conclusion is supported by most studies of atherosclerotic animal models, showing an unchanged or even augmented protein level of eNOS in atherosclerotic arteries, despite the presence of endothelial dysfunction [10-12,13••]. Moreover, studies with human aortic and coronary arterial tissues obtained from autopsy or from transplant donors found only a significantly deceased eNOS gene expression in endothelial cells in advanced but not early atherosclerotic lesions [14,15]. Most recently, a study with human coronary atherectomy specimens showed a higher eNOS gene expression in patients with acute coronary syndromes than those with stable angina [16].…”
Section: Introductionmentioning
confidence: 78%
“…This conclusion is supported by most studies of atherosclerotic animal models, showing an unchanged or even augmented protein level of eNOS in atherosclerotic arteries, despite the presence of endothelial dysfunction [10-12,13••]. Moreover, studies with human aortic and coronary arterial tissues obtained from autopsy or from transplant donors found only a significantly deceased eNOS gene expression in endothelial cells in advanced but not early atherosclerotic lesions [14,15]. Most recently, a study with human coronary atherectomy specimens showed a higher eNOS gene expression in patients with acute coronary syndromes than those with stable angina [16].…”
Section: Introductionmentioning
confidence: 78%
“…[81][82][83] For example, eNOS expression is increased during exercise, 84 and its regulation may help to maintain microvascular health. 85 Recently, HIF-derived increases in skin iNOS expression have been shown to divert blood flow toward the skin, causing a reduction in kidney perfusion and accentuating renal hypoxic responses. 82 Finally, nNOS has been implicated in the regulation of a number of important cardiovascular responses: 1) In the brain, nNOS facilitates synaptic transmission and controls neuronal regulation of HR and mean arterial pressure; 86,87 nNOS can also regulate neurovascular control of cerebral blood flow; 88,89 2) In the heart, nNOS affects contraction and relaxation of cardiac myocytes by regulating intracellular calcium; 90 Fig.…”
Section: Nos-derived No Mediates Cardiovascular Responsesmentioning
confidence: 99%
“…The presence of iNOS mRNA and protein expression has been described in atherosclerotic human plaques in macrophages as well as endothelial and smooth muscle cells [106,162]. In support of a role for iNOS in promoting pathogenesis, iNOS expression was found in the majority of samples as early as the fatty streak stage and in all of the advanced stages of plaques coinciding with an increase in oxidized LDL and nitrated proteins [106].…”
Section: Inducible Nitric Oxide Synthase: Where When and How Much?mentioning
confidence: 92%